137P Comparative analysis of the immune microenvironment in histological subtypes of lung and breast cancer using a tissue microarray (TMA) comprising invasive margin (IM) and tumour centre (TC). (15th December 2019) - Cumberbatch, M; Memeo, L; Womack, C; Kim, W H; Bhagat, M
Abstract: Background: Immunotherapy is proving successful in several tumour settings, although many cancer types remain less responsive. Pre-existing tumour infiltrating lymphocytes and PD-L1 expression associate with response to immunotherapy and cancers have been classified into response subtypes according to these biomarkers. To enable a simultaneous comparative assessment of the immune microenvironment in multiple tumour indications, we have constructed a multi-tumour TMA comprising matched cores for each donor from IM and TC. Methods: In this study, we employed a TMA comprising cores taken from formalin fixed paraffin embedded (FFPE) non-treated surgical resections for donors diagnosed with squamous NSCLC (SCC; n = 13), adeno NSCLC (ADC; n = 12), small cell lung cancer (SCLC; n = 9), oestrogen receptor positive breast cancer (ER+BC; n = 12), Herceptin positive BC (Her2+BC; n = 12) and triple negative BC (TNBC; n = 12). Serial sections were stained by immunohistochemistry for several immune biomarkers (CD163, CD68, PD-L1, CD8, CD3, PD-1, Foxp3, CD4, CD20). Immune infiltrates were analysed by digital image analysis and PD-L1 was scored by a pathologist to deliver both the tumour proportion score (TPS) and the combined positivity score (CPS). Results: By taking an average of all cores (IM and TC) for each disease indication, we demonstrate that SCC, ADC and TNBC are more highly infiltrated, and that while tumour PD-L1 (TPS) was absent in ER+BC and Her2+BC, the contribution from infiltrating immune cells (CPS) was greatest in SCC and TNBC. Interestingly, a reciprocal profile for CD163:CD68 was observed for LC versus BC, with the M2-like CD163+ macrophage/monocytic population exceeding the CD68+ macrophage population in BC, whereas the converse was observed for LC. Immune infiltrates were reduced in TC compared with IM, and distinct case-by-case immune microenvironments were revealed within each disease indication. Conclusion: Using an immuno-oncology focussed TMA we have revealed distinct immune profiles in multiple tumour subtypes simultaneously, providing a valuable basis against which to profile novel immune targets. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: M. Bhagat: Shareholder / Stockholder / Stock options, Officer / Board of Directors: TriStar Technolgoy Group. All other authors have declared no conflicts of interest.